2008
DOI: 10.1007/s10152-008-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-dependent growth in a Caribbean sea urchin Tripneustes ventricosus: the importance of food type

Abstract: The sea urchin Tripneustes ventricosus is a common, yet relatively poorly known, grazer of seagrass beds and coral reefs throughout the Caribbean. We compared the size and abundance of urchins between adjacent seagrass and coral reef habitats (where macroalgae are the dominant primary producers). We also conducted a laboratory experiment comparing the growth rate of juvenile urchins fed a diet of either macroalgae or seagrass. Reef urchins had signiWcantly larger test diameter than those in the seagrass on som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Ordination analysis showed that these patterns in seagrass community composition across years may be related to an inverse pattern in the frequency of occurrence of sea urchins ( Tripneustes ventricosus group), which was minimal in 1994 compared to 1969 and 2016. The importance of sea urchins as major grazers of seagrass and macroalgae is well established [ 67 , 68 ] and some species are known to graze coral recruits [ 69 71 ]. Sea urchins were intensively harvested in Grenada (less so in Carriacou) for export in the early 1990s, leading to the collapse and closure of the fishery by 1995 [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ordination analysis showed that these patterns in seagrass community composition across years may be related to an inverse pattern in the frequency of occurrence of sea urchins ( Tripneustes ventricosus group), which was minimal in 1994 compared to 1969 and 2016. The importance of sea urchins as major grazers of seagrass and macroalgae is well established [ 67 , 68 ] and some species are known to graze coral recruits [ 69 71 ]. Sea urchins were intensively harvested in Grenada (less so in Carriacou) for export in the early 1990s, leading to the collapse and closure of the fishery by 1995 [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…We had previously reported a similar trend for sea urchin gut samples [ 4 ]. The species E. lucunter and D. antillarum inhabit hardgrounds where corals, sponges, and other cnidarians are dominant [ 22 ], while L. variegatus and T. ventricosus usually graze on turtle grass blades ( Thalassia testudinum ) [ 37 ]. The unexpected difference in external microbiota between T. ventriocus and L. variegatus , and the relative similarity between T. ventricosus and the two reefs’ species, could be explained somehow due to the migration behavior of this species [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals of this species were found and collected close to the limit between the seagrass and back reef zones, at approximately 5 m from the border between the two biotopes. T. ventricosus is a common herbivore of seagrass throughout the Caribbean [ 37 ]. Although T. ventricosus is typically associated with seagrass habitats, it has been observed to migrate to the backreef zone where D. antillarum and E. lucunter inhabit [ 70 ], which could explain their relative similarity in gut bacterial composition [ 4 ] and now their epibionts communities too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Второй метод -исследование особенностей роста путем периодических измерений ежей, содержащихся в садках или в аквариумах, либо меченых животных, выпущенных в естественную среду (Pearse and Pearse, 1975;Мина, Клевезаль, 1976;Найденко, Дзюба, 1982;Macia, Robinson, 2008). Этот метод также весьма трудоемок, кроме того, данные по росту, полученные при содержании ежей в контролируемых условиях, не позволяют судить о локальных особенностях их роста в естественной среде.…”
Section: особенности ростаunclassified